Prosedur Pemberian dan Penyelesaian Pembiayaan Bermasalah di KJKS BMT Agam Madani Nagari Batu Palano Kabupaten Agam - Nasfi, Nasfi; Sabri, Sabri; Moni, Rahmah (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This study aims to determine the financing procedures used by KJKS BMT Agam Madani Nagari Batu Palano. Data collection techniques using observation, interviews, and library research using qualitative descriptive methods. The results of this study indicate that the procedure of financing provided by KJKS BMT Agam Madani Nagari Batu Palano Agam Regency can run optimally and in accordance with planned objectives, especially to encourage the efficiency of financing. The efforts that have been carried out by Agam Madani Nagari Batu Palano KJKS BMT Agam Regency to keep the financing provided smooth, productive and non-performing is to comply with every management policy in providing financing.